Answer:
Step-by-step explanation:
#1: True
#2: False
#3: False
#4: False
#5: True
I hope I've helped you.
Answer:
3
−
2
=
1
3v-2=1
3v−2=1
Solve
1
Add
2
2
2
to both sides of the equation
3
−
2
=
1
3v-2=1
3v−2=1
3
−
2
+
2
=
1
+
2
3v-2+{\color{#c92786}{2}}=1+{\color{#c92786}{2}}
3v−2+2=1+2
2
Simplify
Add the numbers
Add the numbers
3
=
3
3v=3
3v=3
3
Divide both sides of the equation by the same term
3
=
3
3v=3
3v=3
3
3
=
3
3
\frac{3v}{{\color{#c92786}{3}}}=\frac{3}{{\color{#c92786}{3}}}
33v=33
4
Simplify
Solution
=
1
Step-by-step explanation: